Development of Practical Creative Movement Skills in Students - M. Akhmedova (Scientific Trends, 2023)
This article talks about the importance of the formation of practical movement skills in teaching creative thinking in primary education and the influence of teachers and parents on the formation of such skills.
Keywords: Creative thinking, creative ability, creative activity, mental ability.